A Versatile Fluoro‐Containing Low‐Bandgap Polymer for Efficient Semitransparent and Tandem Polymer Solar Cells. (15th July 2013) - Chang, Chih‐Yu; Zuo, Lijian; Yip, Hin‐Lap; Li, Yongxi; Li, Chang‐Zhi; Hsu, Chain‐Shu; Cheng, Yen‐Ju; Chen, Hongzheng; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> The versatility of a fluoro‐containing low band‐gap polymer, poly[2, 6‐(4, 4‐bis(2‐ethylhexyl)‐4H‐cyclopenta[2, 1‐b;3, 4‐b']dithiophene)‐alt‐4, 7‐(5‐fluoro‐2, 1, 3‐benzothia‐diazole)] (PCPDTFBT) in organic photovoltaics (OPVs) applications is demonstrated. High boiling point 1, 3, 5‐trichlorobenzene (TCB) is used as a solvent to manipulate PCPDTFBT:[6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71BM) active layer morphology to obtain high‐performance single‐junction devices. It promotes the crystallization of PCPDTFBT polymer, thus improving the charge‐transport properties of the active layer. By combining the morphological manipulation with interfacial optimization and device engineering, the single‐junction device exhibits both good air stability and high power‐conversion efficiency (PCE, of 6.6%). This represents one of the highest PCE values for cyclopenta[2, 1‐b;3, 4‐b']dithiophene (CPDT)‐based OPVs. This polymer is also utilized for constructing semitransparent solar cells and double‐junction tandem solar cells to demonstrate high PCEs of 5.0% and 8.2%, respectively.